Acrodermatitis enteropathica -like syndrome in a subject with pareneteral nutrition. - Garofalo, L.; Colonna, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
A 28-year-old woman was first observed due to acrolocated and periorificial skin lesions. From 10 years of life she had gait and equilibrium disorders, so that after several hospitalizations she had received a diagnosis of cerebello-pyramidal syndrome of likely metabolic origin. She had been clinically stable until August, 2009 when due to dysphagia for solids and liquids, epigastralgia and vomiting, percutaneous endoscopic gastrostomy was performed. In July 2010 she underwent gastric perforation leading to place a central venous catheter and start parenteral nutrition. After 6 months she started to experience limb and periorificial skin lesions, diarrhea and hair loss. The presence of burn-like lesions led us to the determine plasma zinc, that resulted 19 mg/dl (n.v. 70-120). The administration of zinc sulfate 60 mg 3 times daily induced a rapid remission of symptoms, leading to the final diagnosis of acquired acrodermatitis enteropathica-like syndrome.